A LiFePO4 regeneration method based on PVAc alcoholysis reaction. (September 2021) - Guan, Lingyu; Liu, Meihua; Yu, Fan; Qiu, Tao; Zhou, Tangbangguo; Lin, Xu
Abstract: Regeneration of LiFePO4 from spent LiFePO4 cathode material has been proposed by using a new carbon source in the mixture system of methanol and ammonia water. Adding appropriate Li2 CO3, FeC2 O4, and NH4 H2 PO4, the spent LiFePO4 materials were regenerated through high-temperature solid-state reaction with the different amounts of PVAc. Compared with traditional regeneration methods, the addition of carbon sources was greatly reduced in this work. The samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), Raman spectra, X-ray photoelectron spectroscopy (XPS), and electrochemical measurement. According to these results, the regenerated sample with 2.5 wt% PVAc displayed the best morphology, structure, and electrochemical performance. It delivered a high initial capacity of 163.2 mA h g −1 at the rate of 0.1 C, and a high capacity retention of 97.08% at a rate of 0.5 C after 100 cycles, which could meet the commercial requirements of regenerated LiFePO4 batteries to a certain extent. The optimum amount of PVAc still needs further study. Graphical abstract: Image 1 Highlights: Polyvinyl acetate is used to regenerate spent LiFePO4. The preferred addition amount of polyvinyl acetate is 2.5 wt%. Polyvinyl alcohol is released from alcoholysis of polyvinyl acetate. The precursor is mixed and stirred in methanol and ammonia water.